Patient reported symptoms and adverse outcomes seen in Canada's first vaginoplasty postoperative care clinic. Issue 2 (11th January 2023) - Potter, Emery; Sivagurunathan, Marudan; Armstrong, Kathleen; Barker, Lucy C; Du Mont, Janice; Lorello, Gianni R.; Millman, Alexandra; Urbach, David R.; Krakowsky, Yonah
Abstract: Importance: Vaginoplasty is a relatively common gender‐affirming surgery with approximately 200 Ontarians seeking this surgery annually. Although Ontario now offers vaginoplasty in province, the capacity is not meeting demand; the majority of trans and gender‐diverse patients continue to seek vaginoplasty out of province. Out‐of‐province surgery presents a barrier to accessing postsurgical follow‐up care leaving most patients to seek support from their primary care providers or providers with little experience in gender‐affirming surgery. Objective: To provide an account of the common postoperative care needs and neovaginal concerns of Ontarians who underwent penile inversion vaginoplasty out of province and presented for care at a gender‐affirming surgery postoperative care clinic. Design, Settings, and Participants: A retrospective chart review of the first 80 patients presenting to a gender‐affirming surgery postoperative care clinic who had undergone vaginoplasty at an outside surgical center was performed. Descriptive analyses were performed for all variables. Results: The sample consisted of 80 individuals with the mean age of 39 years (19–73). Most patients had surgery at another surgical center in Canada (76.3%). Many patients (22.5%) accessed care in the first 3 months after surgery, with the majority (55%) seeking care within the first perioperative year. Most patients (61.3%) were seen for more than one visit and presented with more than two symptoms or concerns. Common patient‐reported symptoms during clinical visit included pain (53.8%), dilation concerns (46.3%), and surgical site/vaginal bleeding (42.5%). Sexual function concerns were also common (33.8%) with anorgasmia (11.3%) and dyspareunia (11.3%) being the most frequent complications. The most common adverse outcomes identified by health care providers included hypergranulation (38.8%), urinary dysfunction (18.8%), and wound healing issues (12.5%). Conclusions and Relevance: Findings from chart review offer valuable insights into the postoperative needs and neovaginal concerns of Ontarians who have had vaginoplasty out of province. This study demonstrates the need for routine postoperative care in patients undergoing vaginoplasty. Patients experience numerous symptoms and concerns that often correlate with clinical findings and require multiple follow‐up appointments. Health care providers may benefit from further education on the more common nonsurgical issues identified in this study.